Postoperative MRI of the shoulder. Issue 6 (6th February 2014) - Beltran, Luis S.; Bencardino, Jenny T.; Steinbach, Lynne S.
<x xml:space="preserve">Abstract</x> Magnetic resonance imaging (MRI) evaluation of the postoperative shoulder presents technical and diagnostic challenges related to imaging artifacts from hardware and micrometallic shavings, postsurgical scarring, and morphological alterations. Improved visualization of postoperative shoulder anatomy and pathology can be obtained with the use of metal artifact reduction techniques as well as MR arthrography. In this article we review the MR techniques that are designed to address these technical and diagnostic challenges, and we discuss the definitions and indications, normal MRI appearance, and complications of routine surgical procedures for treatment of injuries to the rotator cuff, labral ligamentous complex, and biceps tendon. J. Magn. Reson. Imaging 2014;40:1280–1297. © 2014 Wiley Periodicals, Inc.